Pemanfaatan Sabut Kelapa Sebagai Bahan Dasar Tinta Batik Hitam Melalui ProsesPirolisis: Analisis Kepekatan Warna dan Potensi Ramah Lingkungan Hitam Melalui Proses Pirolisis: Analisis Kepekatan Warna dan Potensi Ramah Lingkungan - PUTRI UNIQA HAPSARI; Heribertus Rudi Kusumantoro; Emmidia Djonaedi (Politeknik Negeri Ketapang, 2025)
Batik is a world-recognized cultural heritage of Indonesia, but the batik industry stillrelies on synthetic dyes that pollute the environment, especially water pollution. Thisstudy aims to develop natural black batik ink from coconut fiber through pyrolysis andanalyze its color density. The process is carried out by heating coconut fiber at 150-250°C to produce charcoal, which is then pulverized into pigments. The pigments weremixed with distilled water (variation of 1-7 g pigment and 6-12 mL distilled water) andtested for density using a spectrodensitometer. The results showed that the formulationof 6 grams of pigment and 11 mL of distilled water produced the highest concentration(2.68). The average concentration of all samples reached 2.57, indicating theconsistency of pigment quality. This study proves that the ratio of pigment and solventaffects color density, while providing an environmentally friendly solution by utilizingcoconut fiber waste as a natural dye with economic value.